PENINGKATAN PEMBELAJARAN DARING MELALUI PENDAMPINGAN GURU DENGAN PEMBUATAN MEDIA PEMBELAJARAN VIDEO ASYNCHRONOUS DI PAUD INKLUSI SAYMARA - Wahyu Wijaya Widiyanto; Dwi Iskandar; Markus Utomo Sukendar (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
The implementation of social distancing in an effort to stop the spread of the Corona virus, a number of schools have eliminated teaching and learning activities, so a study from home policy has been issued by utilizing technology through e-learning to zoom. However, in practice, many complaints are experienced by both students and parents. The purpose of this activity is to provide knowledge and get to know about learning media that attracts students' attention by utilizing media in the form of videos with Power Point, OBS, and Google Meet. This training explores the creativity of PAUD teachers because the teacher plays an important role in attracting students. The benefits of this teacher assistance are inviting teachers and parents to motivate students in learning, the results of this activity itself are videos that have been made or compiled by teachers related to the learning themes that have been prepared according to the material and practice presented, 98% of the participants in the activity convey satisfaction in training events and according to current needs